Buffalo at the crossroads : the past, present, and future of American urbanism - Christensen, Peter H. (Cornell University Press, 2020)
"Buffalo at the Crossroads is a scholarly edited volume comprising essays by twelve authors that investigate the built environment of Buffalo, NY. It provides a new way of looking at the buildings and landscapes in this important American city and beyond, examining the local and global and "high" and "low" contexts of Buffalo's architectural heritage"--